GEOLOGICAL INFLUENCE ON QUALITY OF SELECTED TERTIARY BARITO COAL - BINARKO SANTOSO; BUKIN DAULAY (Puslitbang tekMIRA, 2006)
Type and rank variation within Tertiary Barito coals of Tanjung Formation were analyzed by petro- graphic examination of ten coal samples. Vitrinite, common liptinite and rare inertinite and mi-neral matter dominate all the coals. Vitrinite macerals are dominated by detrovitrinite and telovitrinite. Resinite, cutinite and sporinite are the dominant liptinite macerals in the coals. Inertinite macerals in the coals comprise semifusinite, sclerotinite and inertodetrinite. Mineral matter consists mainly of clay and pyrite. Liptinite and inertinite contents within coals are systematically related to vitrinite content. The liptinite and inertinite contents decrease with increase of vitrinite content. The liptinite content is not related to the inertinite content. Vitrinite reflectance of Palaeogene coals ranges from 0.53% to 0.64% or sub-bituminous to high-volatile bituminous ranks, respectively, as classified by the Australian standards, and of the Neogene ones varies between 0.30% and 0.47%, classified as brown coal and sub-bituminous ranks, respectively. The slight change in vitrinite reflectance from the top to the base of the sequence is due to the thicker cover/overburden on the high rank coals. Similarities and differ- ences in the type and rank of the coals reflect their geological setting.